Antibody Responses with Fc-Mediated Functions after Vaccination of HIV-Infected Subjects with Trivalent Influenza Vaccine - Kristensen, Anne B.; Lay, William N.; Ana-Sosa-Batiz, Fernanda; Vanderven, Hillary A.; Madhavi, Vijaya; Laurie, Karen L.; Carolan, Louise; Wines, Bruce D.; Hogarth, Mark; Wheatley, Adam K.; Kent, Stephen J. (Journal of virology, 2016)
This study seeks to assess the ability of seasonal trivalent inactivated influenza vaccine (TIV) to induce nonneutralizing antibodies (Abs) with Fc-mediated functions in HIV-uninfected and HIV-infected subjects. Functional influenza-specific Ab responses were studied in 30 HIV-negative and 27 HIV-positive subjects immunized against seasonal influenza. All 57 subjects received the 2015 TIV. Fc-mediated antihemagglutinin (anti-HA) Ab activity was measured in plasma before and 4 weeks after vaccination using Fc-receptor-binding assays, NK cell activation assays, and phagocytosis assays. At baseline, the HIV-positive group had detectable but reduced functional Ab responses to both vaccine and nonvaccine influenza antigens. TIV enhanced Fc-mediated Ab responses in both HIV-positive and HIV-negative groups. A larger rise was generally observed in the HIV-positive group, such that there was no difference in functional Ab responses between the two groups after vaccination. The 2015 TIV enhanced functional influenza-specific Ab responses in both HIV-negative and HIV-positive subjects to a range of influenza HA proteins. The increase in functional Ab responses in the HIV-positive group supports recommendations to immunize this at-risk group. IMPORTANCE Infection with HIV is associated with increasing disease severity following influenza infections, and annual influenza vaccinations are recommended for this target group. However, HIV-infected individuals respond relatively poorly to vaccination compared to healthy individuals, particularly if immunodeficient. There is therefore a need to increase our understanding of immunity to influenza in the context of underlying HIV infection. While antibodies can mediate direct virus neutralization, interactions with cellular Fc receptors may be important for anti-influenza immunity in vivo by facilitating antibody-dependent cellular cytotoxicity (ADCC) and/or antibody-dependent phagocytosis (ADP). The ability of seasonal influenza vaccines to induce antibody responses with potent Fc-mediated antiviral activity is currently unclear. Probing the ADCC and ADP responses to influenza vaccination has provided important new information in the quest to improve immunity to influenza.